UV-fs-LA-ICP-MS Analysis of CO2-Rich Fluid Inclusions in a Frozen State: Example from the Dahu Au-Mo Deposit, Xiaoqinling Region, Central China. (4th April 2018) - Jian, Wei; Albrecht, Moritz; Lehmann, Bernd; Mao, Jingwen; Horn, Ingo; Li, Yanhe; Ye, Huishou; Li, Zongyan; Fang, Guanguan; Xue, Yongsheng
Abstract : The recently developed technique of ultraviolet femtosecond laser ablation inductively coupled plasma mass spectrometry (UV-fs-LA-ICP-MS) combined with a freezing cell is expected to improve the analysis of CO2 -rich fluid inclusions by decreasing their internal pressure and avoiding the common problem of uncontrolled explosive fluid release on ablation. Here, we report the application of this technique through the case study of CO2 -rich fluid inclusions from the quartz vein-style Au-Mo deposit of Dahu in the Xiaoqinling region of central China. The concentrations of Li, B, Na, Al, K, Ca, Mn, Fe, Cu, Zn, Rb, Sr, Mo, Ag, Te, Cs, Ba, Au, Pb, and Bi were analyzed in 124 (not all for Al and Ca) fluid inclusions, which have low to moderate salinity and multiphase composition (liquid H2 O + liquid CO2 ± vapor CO2 ± solids). The Dahu fluids are dominated by Na and K. The concentrations of Mo are always below the detection limit from 0.005 to 2 ppm (excluding values obtained from fluid inclusions with accidentally trapped solids). The Dahu ore fluids differ from metamorphic fluids in compositions and most likely represent two separate pulses of spent fluids evolved from an unexposed and oxidized magmatic system. The UV-fs-LA-ICP-MS analysis of fluid inclusions in a frozen state improves the overpressure problem of CO2 -rich fluid inclusions during laser ablation. The transformation of gaseous and liquid CO2 into the solid state leads to a significant decline in the internal pressure of the fluid inclusions, while femtosecond laser pulses generate a minimal heat input in the sample and thus maintain the frozen state during ablation. Transient signals of CO2 -rich fluid inclusions obtained in this study typically had one or multiple peaks lasting for more than 15 seconds, without an initial short signal spike as obtained by ns-LA-ICP-MS analysis of CO2 -rich fluid inclusions at room temperature.